2020
DOI: 10.1177/2473974x20953094
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of a Training Initiative for Nasopharyngeal and Oropharyngeal Swabbing for COVID‐19 Testing

Abstract: Objective The accuracy and reliability of COVID-19 testing are critical to limit transmission. After observing variability in testing techniques, we otolaryngologists at a tertiary medical center initiated and evaluated the impact of nasopharyngeal and oropharyngeal swabbing training, including video instruction, to standardize sampling techniques and ensure high-quality specimens. Methods Participants in the training were employees (N = 40). Training consisted of an instructional video on how to perform nasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, COVID-testing is a relatively simple procedure requiring limited and relatively elementary knowledge and skills, which may indicate a short learning curve that combined with the standardized simulated model may have resulted in some level of ceiling effects. The good effect of a short simulation-based URTS training is also comparable to other studies with similar findings [21,22]. This indicates that URTS is a well-defined procedure where non-healthcare educated workers can perform URT samples comparably to experts if they receive focused and standardized training [23].…”
Section: Discussionsupporting
confidence: 82%
“…However, COVID-testing is a relatively simple procedure requiring limited and relatively elementary knowledge and skills, which may indicate a short learning curve that combined with the standardized simulated model may have resulted in some level of ceiling effects. The good effect of a short simulation-based URTS training is also comparable to other studies with similar findings [21,22]. This indicates that URTS is a well-defined procedure where non-healthcare educated workers can perform URT samples comparably to experts if they receive focused and standardized training [23].…”
Section: Discussionsupporting
confidence: 82%
“…There have been a number of instructional videos for this purpose [ 30 , [35] , [36] , [37] , [38] ]. Simulation programs involving nasopharyngeal swabs have reported a 45–51% increase in levels of self-perceived competence in ability to perform and a 77.5% correct first-attempt swab [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as more HCWs from a diverse background are recruited to perform nasopharyngeal swabs, the appropriateness of doing so without adequate training has been called into question [ [12] , [13] , [14] , [15] ]. Although for the vast majority of cases, the swab is a safe and effective tool to combat the pandemic, HCWs should be aware of the shortcomings of this test.…”
Section: Introductionmentioning
confidence: 99%
“…And more, the results of whole-genome sequencing were identical between the nasopharyngeal swab samples obtained at the previous hospital and our hospital. The well-known reasons for false-negative PCR results are inadequate sampling timing, sampling techniques, storage, transportation, processing of specimens, and technical problems related to the PCR [ 4 , 5 ]. We confirmed that the results of PCR tests varied depending on the type of samples among nasopharynx wiping, suctioned sputum, and tongue wiping samples even obtained on the same day.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although infrequent, false-negative results can lead to misdiagnosis of COVID-19. Inadequate sampling is a well-known reason for false-negative PCR results [ 4 , 5 ]. The duration of SARS-CoV-2 infectivity remains unclear, and it is crucial for understanding transmission dynamics and implementing effective infection control mechanisms.…”
Section: Introductionmentioning
confidence: 99%